2021
DOI: 10.1007/s42452-021-04476-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion and structural properties of some (PbO)x(ZnO)35−x(TeO2)65 glasses

Abstract: The glasses (PbO)x(ZnO)35−x(TeO2)65 with 0 < x < 25 were prepared by conventional melting method. The substitution of ZnO by PbO leads to a decrease in the glass transition temperature (Tg) from 338 to 280 °C and an increase in the linear coefficient of thermal expansion (α) from 15.8 to 19.2 ppm K−1. A correlation between α and Tg has been confirmed by the Lindemann rule. The two prediction methods of the coefficient of thermal expansion (α) were compared with experimental values: the simple additivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This increased stability can limit the formation and mobility of vacancies within the glass network [51] which agrees with the previous data on crystallinity. This finding is consistent with the data of Schwarz et al [52] who found that by increasing the PbO 2 concentration, crystallinity improved.…”
Section: Resultssupporting
confidence: 93%
“…This increased stability can limit the formation and mobility of vacancies within the glass network [51] which agrees with the previous data on crystallinity. This finding is consistent with the data of Schwarz et al [52] who found that by increasing the PbO 2 concentration, crystallinity improved.…”
Section: Resultssupporting
confidence: 93%
“…NBOs weaken the network structure by reducing the number of cross-links between the network formers. This leads to a decrease in the T g of the PbO-TeO 2 -CdO system [44][45][46].…”
Section: Thermal Propertiesmentioning
confidence: 99%